Hosting the 2010 Vancouver Olympic Games and wellbeing among Canadian youth - Teare, G.; Potwarka, L. R.; Bakhsh, J. T.; Barrick, S. J.; Kaczynski, A. T. (European Sport Management Quarterly, 2021)
Research question: Although research traction is increasing, intangible social impacts are still difficult to measure and relatively under-researched compared to their tangible economic counterparts. Thus, the current study examines the question: what were the associations between hosting the 2010 Vancouver Olympic Games, social wellbeing (i.e. sense of belonging), and subjective wellbeing (i.e. life satisfaction) among Canadian youth? Research methods: Using data from the Canadian Community Health Survey (n > 1,000,000), a time series analysis of youths` (aged 12-19) reports of perceived sense of belonging to their community and perceived life satisfaction across four time points before and after the Vancouver Winter Olympic and Paralympic Games at the national, provincial, and regional levels was conducted. Research findings: The number of youths who reported a strong sense of belonging to their community significantly increased in the host region of North Shore after the Games concluded (2011-2012 to 2013-2014). The number of youths who reported a strong sense of belonging to their community and high life satisfaction significantly increased from 2007-2008 (pre-event) to 2009-2010 in the host region of Richmond. Implications: This study provides preliminary evidence that mega-sport events might positively affect wellbeing of youth living in regions that house venues for the event. The study also demonstrates the temporary nature of positive social impacts. Suggestions for how to help create situations where positive social impacts are more likely, and to help maintain the wellbeing benefits of mega-sport events for youth populations are offered.